Effects of Manual Therapy on Patients with Functional Constipation: Systematic Review and Meta-analysis of Randomized Clinical Trials. - Torres-Sánchez, Irene; Ramírez Zafra, Andrea; Rueda García, Elisabet; Cabrera-Martos, Irene; Díaz-Mohedo, Esther (Elsevier, 2025)
Objective: The aim of this study was to analyze the effects of manual therapy techniques on adults with functional constipation (FC). Methods: Four databases (CINAHL, PubMed, Scopus and Web of Science) were searched up to May 2025. Inclusion criteria were defined following PICOS recommendations. Methodological quality was assessed with the Downs and Black scale, and the risk of bias was evaluated with the Cochrane risk of bias assessment tool. The meta-analysis was performed using RevMan 5.4 software. Results: Fifteen randomized clinical trials with a total of 859 patients were included in the systematic review and eleven were included in the meta-analysis. Manual therapy compared to no manual therapy significantly improved constipation severity, constipation status, quality of life (QOL), defecation frequency, and defecation duration. In addition, abdominal massage compared to no manual therapy significantly improved constipation severity. Manual therapy, compared to a control intervention, significantly improved constipation severity. Manual therapy applied alone or combined with another treatment showed significant differences compared to no manual therapy. Conclusion: Manual therapy, compared to no manual therapy, significantly improved constipation severity and status, QOL and defecation frequency and duration in adults with FC without any other pathology. In addition, abdominal massage compared to no manual therapy and manual therapy compared to a control group also significantly improved constipation severity. Similar significant differences were also found in favor of manual therapy when it was applied alone or combined with another treatment. High heterogeneity between studies affected the consistency of results, therefore these findings should be considered with caution.
Effects of Manual Therapy on Patients with Functional Constipation
Keywords: Estreñimiento - Tratamiento; Masaje terapéutico; Manipulación (Terapéutica); Constipation; Manual therapy; Massage